NRT1.1-Related NH(4)(+) Toxicity Is Associated with a Disturbed Balance between NH(4)(+) Uptake and Assimilation - Jian, Shaofen (Plant Physiol, 2018)
A high concentration of ammonium (NH(4)(+)) as the sole source of nitrogen in the growth medium often is toxic to plants. The nitrate transporter NRT1.1 is involved in mediating the effects of NH(4)(+) toxicity; however, the mechanism remains undefined. In this study, wild-type Arabidopsis (Arabidopsis thaliana Columbia-0 [Col-0]) and NRT1.1 mutants (chl1-1 and chl1-5) were grown hydroponically in NH(4)NO(3) and (NH(4))(2)SO(4) media to assess the function of NRT1.1 in NH(4)(+) stress responses. All the plants grew normally in medium containing mixed nitrogen sources, but Col-0 displayed more chlorosis and lower biomass and photosynthesis than the NRT1.1 mutants in (NH(4))(2)SO(4) medium. Grafting experiments between Col-0 and chl1-5 further confirmed that NH(4)(+) toxicity is influenced by NRT1.1. In (NH(4))(2)SO(4) medium, NRT1.1 induced the expression of NH(4)(+) transporters, increasing NH(4)(+) uptake. Additionally, the activities of glutamine synthetase and glutamate synthetase in roots of Col-0 plants decreased and soluble sugar accumulated significantly, whereas pyruvate kinase-mediated glycolysis was not affected, all of which contributed to NH(4)(+) accumulation. By contrast, the NRT1.1 mutants showed reduced NH(4)(+) accumulation and enhanced NH(4)(+) assimilation through glutamine synthetase, glutamate synthetase, and glutamate dehydrogenase. Moreover, the up-regulation of genes involved in ethylene synthesis and senescence in Col-0 plants treated with (NH(4))(2)SO(4) suggests that ethylene is involved in NH(4)(+) toxicity responses. This study showed that NH(4)(+) toxicity is related to a nitrate-independent signaling function of NRT1.1 in Arabidopsis, characterized by enhanced NH(4)(+) accumulation and altered NH(4)(+) metabolism, which stimulates ethylene synthesis, leading to plant senescence.